(untitled) (World Economics and Finance Bulletin, 2023)
Many production systems have emerged that seek to achieve quality and competitive advantage, including the Lean Production system, which is the next step for the production system on time to rationalize the consumption of resources within the production process by eliminating losses in all its forms and thus providing cleaner production. The research aims to shed light on some theoretical aspects of Lien Production and Cleaner Production, such as advanced manufacturing techniques adopted by companies in developed countries. And a statement of the role of measuring soft production in achieving competitive advantage by providing cleaner production to enhance the market position of the economic unit and improve the flow during production processes and develop them through continuous improvement programs, in addition to achieving many advantages, including reducing waiting times and increasing the level of productivity and others. The study was based on the hypothesis that there is that the use of Linian production aims to provide cleaner production and thus improve competitive advantage, and to prove this was studied cleaner production and Lini production in terms of the theoretical framework of each of them and the provision of new products sustainable and measure the costs of production Lini and their role in achieving competitive advantage in light of environmental changes and achieving continuous improvement of the performance of various operations in the economic unit to maintain its survival and continuity and support its competitive position. In light of this, a set of conclusions and recommendations related to the subject of the study were reached, the most important of which were: The use of soft production achieves profit and economic savings by reducing costs, increasing labor efficiency and production quality, reducing waste and preventing pollution and its effects, which leads to achieving cleaner production and thus raising the possibility of competition. The need to use different units of measurement in expressing data related to soft production to be an integrated picture that helps in the decision-making process, and this does not mean limiting these costs to a specific model, but constantly changing the model according to trends..